Risk Analysis from Failure Occurrences of the Sea Freight Import Process: A Case Study of a Logistics Service Provider Company in Thailand - Monthatipkul, Chumpol; Sriboonsong , Chatchasa; Sae-Lim, Patipan (Business Administration and Management Journal Review, 2023)
Failure Mode and Effect Analysis (FMEA) in order to determine risks represented by the Risk Priority Number (RPN). The study covered investigation of the failures within the current processes, root cause analysis, severity levels, occurrence frequencies, and ability of failure detection. They were prioritized by the RPN, which was a product of severity level score, occurrence frequency score, and detection ability score. It was found that the case study had twelve main working processes and eight of them could be improved if actions were performed correctly. The risks of failures could be decreased if there existed suitable working procedures, training, task review, responsibility assignment, a statistics-based performance evaluation system, punishment, assistance software, task review by leaders, and request for goods and vehicle details. There were four working processes in which the case study must conduct good preparation and accept those corresponding risks. No necessary actions were required due to uncontrollable factors from external sources. Then, the proposed actions for six selective processes were implemented. After implementation of trial versions of the proposed actions, it was found that all of the selective processes performed better.